2020
DOI: 10.1101/2020.01.08.898668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial carotenoids suppressCaenorhabditis eleganssurveillance and defense of translational dysfunction

Abstract: Microbial toxins and virulence factors often target the eukaryotic translation machinery.Caenorhabditis elegans surveils for such microbial attacks by monitoring translational competence, and if a deficit is detected, particular drug detoxification and bacterial defense genes are induced. The bacteria Kocuria rhizophila has evolved countermeasures to animal translational surveillance and defense pathways. Here, we used comprehensive genetic analysis of Kocuria rhizophila to identify the bacterial genetic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…We found that the C. glutamicum (X spectrum in Figure 12B) and K. rhizophila (Z spectrum in Figure 12D) pigment absorption spectra exhibited three major absorption peaks that are representative of decaprenoxanthin absorption at 413 nm, 437 nm and 467 nm as described in the literature. [29][30][31] These three absorption peaks from C. glutamicum absorption spectrum X and K. rhizophila absorption spectrum Z very nicely overlaid against the three absorption peaks from the Clip185 absorption spectrum (Y spectrum in Figure 12B and Figure 12D). This result very strongly indicates the presence of decaprenoxanthin in Clip185.…”
Section: Spectrophotometric Analyses Of Pigments Synthesized By Clip185mentioning
confidence: 83%
See 3 more Smart Citations
“…We found that the C. glutamicum (X spectrum in Figure 12B) and K. rhizophila (Z spectrum in Figure 12D) pigment absorption spectra exhibited three major absorption peaks that are representative of decaprenoxanthin absorption at 413 nm, 437 nm and 467 nm as described in the literature. [29][30][31] These three absorption peaks from C. glutamicum absorption spectrum X and K. rhizophila absorption spectrum Z very nicely overlaid against the three absorption peaks from the Clip185 absorption spectrum (Y spectrum in Figure 12B and Figure 12D). This result very strongly indicates the presence of decaprenoxanthin in Clip185.…”
Section: Spectrophotometric Analyses Of Pigments Synthesized By Clip185mentioning
confidence: 83%
“…as anti-oxidants and light harvesting pigments, photo-protection, acting as membrane stabilizers or repressors of translational surveillance and defense pathways in nematodes etc.). 29,67,68 Commercially, carotenoids are used as food colorants, animal feed supplements, cosmetics, antioxidants and other health supplements. 67,69 Pathways and related enzymes for carotenoid biosynthesis are well characterized (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three maximum absorption peaks of decaprenoxanthin were monitored at 413 nm, 437 nm and 467 nm, as described for decaprenoxanthin and its glucosides in the literature. 30 32 C. glutamicum and K. rhizophila were used as positive controls in spectrophotometric analyses. Three biological replicates per strain were used in this experiment.…”
Section: Methodsmentioning
confidence: 99%